Football Observers' Perceptions of Women's Football in Aceh - Sarwita, Tuti; Shima, Nurzatul; Is, Zulheri; Pranata, Didi Yudha; Rahmat, Zikrur; Irfandi, Irfandi; Munzir, Munzir; Hariansyah, Septi; Irwandi, Irwandi (Jurnal Ilmiah Teunuleh, 2023)
The presence of women's football in Aceh is against the MPU because according to them women's football is not in accordance with Islamic law. With this, this study aims to determine how the perceptions of football observers in Aceh on the formation of women's football teams in Aceh. Respondents in this study were divided based on 4 criteria consisting of, (1) Perspectives of football lovers, (2) According to the point of view of the Football Coach, (3) Viewpoints of Football Players, (4) Perspectives of Sports Managers. Collecting data in this study using a closed questionnaire system with the aim of knowing the perceptions of football observers in Aceh which are divided into 3 things, namely, in terms of facilities and infrastructure, referees, and cultural / cultural aspects. Based on the results of data processing in this study, the data of this study were presented using a Likert scale with the results that answered strongly disagree 4.8%, disagree 8.8%, agree 22.7%, and strongly agree 63.7 to existence. Women's Football in Aceh. This research can conclude that the perception of football observers on women's soccer in Aceh is positive.